(untitled) (Revista de História da UEG (REVHIST), 2024)
The objective of the article is to investigate the connections of the political projects of Alba and Wessex available from the narratives of two insular chronicles. The Anglo-Saxon Chronicle, written at the behest of Ælfred of Wessex (r. 871 – 899) in Winchester, had a common stock completed around 892, when its contemporary writing began and continued until 1054. The Chronicle of the Kings of Alba had a common stock completed around 971 during the reign of Cináed II mac Mael Choláim (r. 971 – 995), but with content that dates back to the reign of Cináed I mac Ailpín (r. 843 – 858). Under the methodology of Connected Histories, we inquire: which narratives can be connected by the political projects of Wessex and Alba? In the descriptions of the documents, two points interconnect the narratives: 1) the construction of power projects for internal cohesion of their respective realms; 2) the establishment of ethnic unity in the face of the threat from external agents. Keywords: Insular chronicles. Narrative. Connected Histories. Wessex. Alba.